Rosacea and Dry Eye Disease. (3rd April 2022) - Sobolewska, Bianka; Schaller, Martin; Zierhut, Manfred
ABSTRACT: Ocular rosacea is a chronic potentially sight-threatening inflammatory condition, which can occur in approximately 20% of patients without skin involvement. However, an accurate diagnosis of ocular rosacea has not been defined yet due to its rather nonspecific symptoms and clinical findings. Therefore, this article updates the current recommendations for diagnosis and treatment of ocular rosacea and the previously published consensus recommendations from the ROSCO expert panel on the management of rosacea.